Lifting device for underground detection - LI HEXUE (2024)
The utility model provides a lifting device for underground detection, and relates to the technical field of lifting devices.The lifting device comprises two sets of side plates with the same specification, supporting legs are installed on the outer side faces of the side plates, auxiliary fixing assemblies are arranged on the surfaces of the supporting legs, steel rope winding rollers are rotationally arranged on the opposite inner sides of the side plates, and transverse plates are installed on the opposite inner sides of the side plates; a driving motor is installed on the upper end face of the transverse plate, a control host is installed on the upper end face of the transverse plate, a guiding measuring assembly is arranged below the transverse plate, the guiding measuring assembly is used for guiding the wound and unwound steel rope and measuring displacement, a user can conveniently know the lowering depth of the detection base, and the detection base can ascend or descend more stably; the ground nail